Effects of postpartum treatment with non-steroidal anti-inflammatory drugs on milk production and culling risk in dairy cattle - Carpenter, Abigail J.; Ylioja, Caroline M.; Vargas, Claudio F.; Mamedova, Laman K.; Mendonca, Luis; Coetzee, Johann F.; Hollis, Larry C.; Gehring, Ronette; Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2015)
Inflammation during early lactation is common in dairy cattle, and a high degree of inflammation during this time has recently been associated with both lower productivity and greater risk of disease during that lactation. Early lactation treatments with two non-steroidal anti-inflammatory drugs were compared with a placebo treatment to evaluate effects on whole-lactation productivity and retention in the herd. Both meloxicam and sodium salicylate increased whole-lactation milk and milk protein yields by 6 to 9%, despite being administered for only 1 or 3 days in early lactation, respectively. In addition, meloxicam treatment tended to decrease the risk of cows leaving the herd during the lactation. These results indicate that postpartum inflammatory signals have long-lasting effects on lactation in dairy cattle.
Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Transition dairy cow; Inflammation; Non-steroidal anti-inflammatory drug